Minimizing Nail Distribution Routes Using the Ant Colony Optimization Method With MATLAB - Mulyani, Mochammad Raihan; Aryanny, Enny (Journal La Multiapp, 2024)
This research aims to determine the delivery route for nails to minimize the total distribution distance in CV. XYZ. This research method is quantitative with primary data analysis consisting of consumer location, distance between consumers, vehicle capacity and product demand data. The findings from this research are that the most optimal route was obtained after running the MATLAB program using the Ant Colony Optimization Algorithm with the most optimal distance of 99 Km. The difference distance between the company's method and the proposed method is 70.4 km, fuel consumption difference is 8,8 liters, fuel cost difference is IDR 59.840, with a percentage savings is 41.5%. Factors that influence this success include choosing a route that is different from the company's initial route so that optimizing the route obtained from the Ant Colony Optimization Algorithm produces optimal and effective results. Factors that influence this success include choosing a route that is different from the company's initial route so that optimizing the route obtained from the Ant Colony Optimization Algorithm produces optimal and effective results. Recommendations for further research are that researchers analyze the results from using 2 methods or add variables that will help the research process in the future, such as road conditions or vehicle performance in carrying out distribution.